MT Post-editing: A Text Repair Experience for the Foreign Language Class. - Niño, Ana (Cadernos de Tradução, 2007)
Communication also means having to sort out the problems involved in learning a foreign language, especially with regards to production rather than reception. These learning strategies or skills can also be applied to translation teaching methodology, where students put in practice their risk taking, avoidance, reduction and/ or compensatory strategies in getting the message across. We acknowledge translation as a writing task constrained by the source text. In addition, the translation and the writing cycles have in common a generation stage and a revision stage where grammatical, lexical and stylistic correctness is assessed. Somewhere in the middle between translation and writing skills lies MT (Machine Translation) post-editing that involves correcting the raw MT output with the aim of providing a quality text according to the intended purpose. Our research is intended to test the suitability of MT post-editing as an activity to promote error correction and, subsequently, to enhance written production in second and foreign language teaching.